PENDEKATAN HOLISTIK DALAM PENANGANAN LANSIA TERLANTAR : STUDI LITERATUR TENTANG MODEL INTERVENSI PEKERJAAN SOSIAL - Derek Bakarbessy (JURNAL BADATI, 2024)
This study aims to analyze the holistic approach in handling neglected elderly through a systematic literature review of 85 scientific articles published between 2019-2024. The research method used the PRISMA protocol with inclusion criteria that included articles in Indonesian and English that focused on intervention models for neglected elderly. The results identified five main intervention models, with community-based models showing the highest effectiveness (32.9%), followed by integrated models (27.1%), psychoeducation (17.6%), empowerment (14.1%), and multi-level (8.2%). A holistic approach that integrates physical, psychological, social, and economic dimensions showed an improvement in health status by 68.5%, a decrease in depression levels from 65% to 28%, an increase in social participation by 75.3%, and an increase in economic independence by 45.2%. Supporting factors for success include multi-stakeholder collaboration (82.5%), increased capacity of social workers (73.8%), and a structured monitoring system. The main challenges include limited resources (68.5%), inter-agency coordination (57.2%), and program sustainability (63.8%). This study recommends strengthening community-based approaches with local context modifications and developing a comprehensive policy framework to support sustainable program implementation.